2015
DOI: 10.1097/htr.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Global Outcome Trajectories After TBI Among Survivors and Nonsurvivors

Abstract: Objective To compare long-term functional outcome trajectories of individuals with traumatic brain injury (TBI) who survive with those who expire more than 5 years postinjury, using individual growth curve analysis. Design Secondary analysis of data from a multicenter longitudinal cohort study. Setting Acute inpatient rehabilitation facilities that are current or former TBI Model Systems. Participants Individuals 16 years and older with a primary diagnosis of TBI. Main Outcome Measures Glasgow Outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 36 publications
1
7
2
Order By: Relevance
“…Contrary to our hypothesis, the HLM of the quadratic GOSE score trajectories showed a significant change over time, with an initial increase and then decrease in GOSE scores up to 10 years after injury. These findings are partly consistent with two larger US studies looking at GOSE trajectories up to 20 years after TBI ( 18 , 19 ), which found initial improvement in functional status before a peak, and a decline in GOSE scores. However, the decline started after the 10-year follow-up.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Contrary to our hypothesis, the HLM of the quadratic GOSE score trajectories showed a significant change over time, with an initial increase and then decrease in GOSE scores up to 10 years after injury. These findings are partly consistent with two larger US studies looking at GOSE trajectories up to 20 years after TBI ( 18 , 19 ), which found initial improvement in functional status before a peak, and a decline in GOSE scores. However, the decline started after the 10-year follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…A Swedish study ( 16 ) reported no significant difference in GOS outcome between 1 year and 10–15 years in survivors after severe TBI; similarly, a recent Norwegian study ( 17 ) found stable global functioning between 10 and 20 years after moderate to severe TBI. These Scandinavian findings of stable levels of disability are contrary to the findings in two large TBIMS studies ( 18 , 19 ) that reported initial improvement in functional status up to approximately 10 years after injury, followed by a peak and a decline in GOSE scores (i.e., increasing disability).…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Survey development. Survey items are based in part on evidence-based clinical guidelines published by the American Association of Neuroscience Nurses (American Association of Neuroscience Nurses, 2008) and in part on the broader TBI outcomes literature (Corrigan et al, 2007;Dams-O'Connor, Pretz, Billah, Hammond, & Harrison-Felix, 2015;Lunney, McGuire, Endozo, & McIntosh-Waddy, 2010;Saban, Smith, Collins, & Pape, 2011). The first draft of survey items generated for the PBIS was distributed to five registered nurses, a PhD-prepared nurse, a physician, and a statistician.…”
Section: Perceptions Of Brain Injury Survey (Pbis)mentioning
confidence: 99%
“…The estimated global prevalence of chronic impairments secondary to TBI was 55.5 million cases in 2016 2 . In the U.S. alone, over 2.7 million TBIs occur each year, leading to approximately 288,000 TBI-related hospitalizations 3 and resulting in long-term disability among both civilian 4 and military 5 populations. Residual motor deficits in the chronic phase of TBI are common and can be especially disabling.…”
Section: Introductionmentioning
confidence: 99%